Mutation update for CYP4F22 variants associated with autosomal recessive congenital ichthyosis. Issue 10 (7th August 2018) - Hotz, Alrun; Bourrat, Emmanuelle; Küsel, Julia; Oji, Vinzenz; Alter, Svenja; Hake, Lisanne; Korbi, Mouna; Ott, Hagen; Hausser, Ingrid; Zimmer, Andreas D; Fischer, Judith
Abstract: Autosomal recessive congenital ichthyosis (ARCI) is a heterogeneous group of rare disorders of keratinization characterized by generalized abnormal scaling of the skin. Ten genes are currently known to be associated with ARCI: TGM1, ALOXE3, ALOX12B, NIPAL4 ( ICHTHYIN ), ABCA12, CYP4F22, PNPLA1, CERS3, SDR9C7, and SULT2B1 . Over a period of 22 years, we have studied a large patient cohort from 770 families with a clinical diagnosis of ARCI. Since the first report that mutations in the gene CYP4F22 are causative for ARCI in 2006, we have identified 54 families with pathogenic mutations in CYP4F22 including 23 previously unreported mutations. In this report, we provide an up‐to‐date overview of all published and novel CYP4F22 mutations and point out possible mutation hot spots. We discuss the molecular and clinical findings, the genotype–phenotype correlations and consequences on genetic testing. Abstract : Autosomal recessive ichthyosis (ARCI) is a heterogeneous group of rare disorders of keratinization characterized by general abnormal scaling of the skin. Ten genes are currently known to be associated with ARCI: TGM1, ALOXE3, ALOX12B, NIPAL4, ABCA12, CYP4F22, PNPLA1, CERS3, SDR9C7, and SULT2B1 . In this mutation update, we review the current state of our knowledge of CYP4F22 mutations and present 23 previously unpublished mutations. We examine the molecular and clinical findings and discuss the genotype‐phenotype correlation.